Perempuan dan Kekristenan pada Masyarakat Tolaki dan Moronene di Sulawesi Tenggara, 1915-1946 - Basrin Melamba (Department of History, Faculty of Humanities, Diponegoro University, 2020)
This study discusses the role of zending women or wives of European priests during the Dutch East Indies (1915-1942) in Southeast Sulawesi. The wives of zending women provide a big contribution or role for the advancement of the indigenous population. The woman is present on the stage in the religious arena by providing social services which has had a major influence on social change in society in Southeast Sulawesi. Women and zending wives act as agents and actors who assist their husbands in carrying out social service programs such as health education in the form of handling pregnant women, postpartum, care and medication, provision of sewing skills, cooking, baking and so on. This changes the lifestyle of indigenous women to be present in the public world, without forgetting their main responsibility. This research argues that zending women contribute or play a role in the advancement of the indigenous population, as well as bring about socio-cultural changes. The role of women in the stage of the religious arena by providing social services has had a major influence on the natives. The conclusion is that the role of zending women in carrying out services causes social change among indigenous Tolaki and Moronene women.